2016
DOI: 10.1158/0008-5472.can-15-2665
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Lin28/let-7 Axis by Loss of ESE3/EHF Promotes a Tumorigenic and Stem-like Phenotype in Prostate Cancer

Abstract: Although cancer stem-like cells (CSC) are thought to be the most tumorigenic, metastatic, and therapy-resistant cell subpopulation within human tumors, current therapies target bulk tumor cells while tending to spare CSC. In seeking to understand mechanisms needed to acquire and maintain a CSC phenotype in prostate cancer, we investigated connections between the ETS transcription factor ESE3/EHF, the Lin28/ let-7 microRNA axis, and the CSC subpopulation in this malignancy. In normal cells, we found that ESE3/E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 51 publications
1
82
0
Order By: Relevance
“…Tumor growth was monitored with a caliper and in vivo bioluminescence imaging using an IVIS Spectrum (Caliper LifeSciences). Ex vivo assays to assess stem-like cancer cells in tumor tissues were performed as previously described (36,37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor growth was monitored with a caliper and in vivo bioluminescence imaging using an IVIS Spectrum (Caliper LifeSciences). Ex vivo assays to assess stem-like cancer cells in tumor tissues were performed as previously described (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…To test our hypothesis, we assessed the fraction of stem-like cancer cells in tumor xenografts after OPB-51602 treatment using ex vivo flow cytometry and tumor-sphereforming assays (36,37). These assays reliably monitor the stemlike cancer cell subpopulation in tumor xenografts, showing high correlation with the tumorigenic capability of stem-like cancer cells in vivo (36,37). Notably, the fraction of CD44…”
Section: Proteotoxic Stat3 Aggregate Formation and In Vivo Antitumormentioning
confidence: 99%
“…1e; Supplementary File2). For example, Nmi (N-myc interactor), known to interact directly with Sox10 31 and inhibit canonical Wnt signalling in cancer cell lines 32 , showed increased expression at T20, while EHF (Ets homologous factor, also known as Epithelial Specific Ets-3), proposed to play a role as a tumour-suppressor in prostate cancer 33 and oncogene in ovarian cancer 34 , showed greatly elevated expression at T21. Fli1 and Satb2, which are both known to be expressed in the developing branchial arch cartilage and mesenchyme [35][36][37] , and Nfatc, which has been shown to form a complex with Sox10 during Schwann cell differentiation 38 , were also elevated at T21.…”
Section: Dynamics Of the Developing Neural Crest Transcriptomementioning
confidence: 99%
“…A subset of ETS factors known as epithelium-specific ETS (ESE) factors, including ESE1 (Ert/Jen/Elf3/Esx), ESE2 (Elf5), ESE3 (EHF), and Pdef (Pse), are expressed in epithelial tissues (12). Authors reported that ESE3 in particular binds directly to target genes to control epithelial-to-mesenchymal transition (EMT), stem-like features (13,14), and tumor progression (1517). Feldman and coworkers have analyzed the expression patterns of ESE factors in diverse types of tissues and cell lines, and found that in normal human pancreas only ESE1 and ESE3 but not ESE2 and Pdef proteins are expressed (5).…”
Section: Introductionmentioning
confidence: 99%